Analisis Penerapan Sistem Informasi Akuntansi untuk Meningkatkan Efisiensi dan Keamanan Keuangan UMKM (Cafe Rindu Lokaria) - Sisilia Anyel Faridawati; Henrikus Herdi; Paulus Libu Lamawitak (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
The research aimed to analyze how the implementation of the Accounting Information System (AIS) can improve financial efficiency and security at Rindu Lokaria Cafe which currently still manages finances manually. The method used in this research involved qualitative analysis through interviews and direct observation of the financial process at Rindu Lokaria Cafe. This research found that the lack of understanding and implementation of AIS at Rindu Lokaria Cafe led to inaccuracies in recording transactions, difficulties in inventory management, and high risks to financial data security. The results of this research stated that effective AIS implementation as proven to provide several significant benefits, including reduced errors in recording, increased operational efficiency, and better protection of financial data. AIS can hel Rindu Lokaria Cafe improve its financial performance and minimize the risks associated with manual management. This research suggest that Rindi Lokaria Cafe and other MSMEs in Indonesia consider implementing AIS as a strategic step to improve their financial efficiency and security, which will support their business growth and sustainability.